An analysis of house price index as the alternative pricing benchmark for Islamic home financing - Redzuan, Nur Harena; Kassim, Salina (Springer Nature Singapore Pte Ltd, 2018)
Currently, major interest rates, such as the Base Lending Rate (BLR) and Kuala Lumpur Interbank Offered Rate (KLIBOR) are widely used as reference rates by the Islamic financial institutions to benchmark a broad range of financial products and contracts. This study aims to compare the viability of an alternative pricing mechanism for Islamic home financing products. In achieving its objective, the study tests the relationships between current interest rate benchmark and house price with the economic variable. The study focuses on Malaysia as a case study and uses quarterly data frequency covering the period from 2001 to 2015. Specifically, the study compares the Base Lending Rate (BLR) and Housing Price Index (HPI) with the economic growth as the main indicator for economic activity. Through the correlation analysis, the study finds that the non-interest benchmark shows better relationships with macroeconomic variable compared to the interest-based benchmark, indicating that the alternative benchmark has a stronger link to the economic movements. The ARDL regression analysis reveals that the house price has a significant relationship with economic growth in Malaysia case. The findings of this study would provide important insights into the viability of house price index as the alternative to the benchmark of the equity financing home financing product. This study contributes to the empirical evidence on the feasibility of adopting the interest-free benchmark to price Islamic home financing products.